Competences of Special Pedagogue and Their Improvement Opportunities from the Point of View of Pedagogues - Urnėžienė, Emilija; Budrytė, Kristina (Pedagogika, 2014)
Rapid changes in economy, social relations as well as globalisation, development of information and communication technologies impose new challenges on a teacher, who is a mediator between changes in education and processes of society improvement. Working with special learning needs students, a special pedagogue assists such learners in adopting content of education and develops their impaired functions, collaborates with their parents as well as teachers providing them with methodological support and consulting, develops individual, sub-group and group programmes for development of impaired functions of children, advice teachers regarding special education issues and others. More successful implementation of these activities requires certain competences of special pedagogue, which are outlined in the Description of Teacher Professional Competences and embrace: common cultural, professional and generic ones. The goal of the research: to reveal attitudes of special pedagogue of general education schools towards competences of special pedagogue and their improvement opportunities. The object of the research: competences of special pedagogue of general education schools. The methods of research: 1) analysis of scientific literature, 2) questionnaire survey, 3) statistic analysis of research data. The sample of the research included 244 special pedagogues from general education schools of various counties of Lithuania. In the first stage of the analysis the respondents were asked to express own attitudes towards competences of a special pedagogue. In the second stage of the analysis the special pedagogues pointed out what predetermines success in the process of education, where a special pedagogue works with learners of special educational needs. The third stage focused on identification of possibilities of professional development of special pedagogues, needs for competence development and, therefore, the respondents were requested to express own opinion about conditions, which are necessary to obtain competences of highest level. The research data revealed that for a special pedagogue, who works with special needs learners, it is most important to possess positive personal features (patience, tolerance, humanity, comprehensiveness, consistency, etc.) and all the professional competences, particularly focusing on competences of communication and collaboration, learners’ motivation and support to them, learner’s cognition and his/her acknowledgement and professional development. Personal motivation of a pedagogue, which embraces a wish to help, love for job, positiveness, development, is also of utmost importance. According to special pedagogues, a number of changes, such as reduction of workload, increase of financing, renewal of workplace, support from administration, provision with methodological aids, collaboration and changes in education may result in acquisition of competences of highest level. The paradigm of continuous development is also emphasized and its calls for personal, professional and social lifelong development. Continuous improvement ensures high quality activities of special pedagogue, which have influence not only on achievements of special needs learners but also on changes occurring in the society. Therefore, a special pedagogue has to be a constantly learning personality. In the context of constant changes, learning acquires features of a permanent process.